Influencia de dos aditivos en la respuesta productiva y sanitaria de cerdos en crecimiento-ceba - Flores Mancheno, Luis Gerardo; García Hernández, Yaneisy; Caicedo Quinche, William Orlando; Usca Méndez, Julio Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 65-73.